ANÁLISE DO TURISMO AMBIENTAL EM MUNICÍPIOS GOIANOS - Janete Rêgo Silva; Nilson Clementino Ferreira (Boletim Goiano de Geografia)
The state of Goiás has a big importance to Biome Cerrado, with 97 % of his territory on this Biome. The proportionof the occupancy and conversion of biome in Goiás indicate the necessity of an environment policy that beholdactions of conservation of the biodiversity and the sustainable of development of the community and thetourism is the strategic themes for this policy. The objective of this paper is to characterize the municipalitywith environment tourism in relation to social, economic and institutional variable. The method of this paperconsisted on survey socioeconomic and environment data, forthwith the treatment and analyses of this data onthe GIS. The analyze of this data possibility to identify of the municipality that has better infrastructure of theenvironment, social and economic for the tourism.